Analysis of the Decision of the Industrial Relations Court in the Dispute for Termination of Employment (Case Study No. 060 / Pdt.Sus-Phi/2023/Pn Mdn Juncto Verdict Number :1174k / Pdt.Sus-Phi/2023 ) - Elina, Elina; Kusbianto, Kusbianto; Ruslan, Ruslan (International Asia Of Law and Money Laundering (IAML), 2024)
This study is motivated by the frequent cases of agreement disputes between companies and workers, especially in the case of termination of employment relationships for both permanent and contractual workers or commonly known as a specific time work agreement, which often ends up at the green table due to differences in understanding between employers and workers as well as differences in understanding of applicable laws and regulations.In addition, there are times when it is also caused by the inability of one party to fulfill its obligations which may be caused by conditions in which the company experiences losses or due to bankruptcy conditions. This paper aims to analyze the legal process that occurs in the case of termination of employment lawsuit ranging from the mediation level , the Medan state court to the Supreme Court of the Republic of Indonesia and find out the basic consideration of judges used in making decisions in accordance with the principle of justice in the case of Decision No. 060 / Pdt.Sus-PHI/2023/PN MDN juncto decision No. 1174K / Pdt.Sus-PHI/2023. This research is Notmatif legal research with normative juridical approach . The data source of this study comes from secondary data.Data collection tool is done with the study of literature (library research). Based on the results of the research conducted , we conclude that the process of termination of employment with bankruptcy conditions, the employer must pay a certain amount of money in accordance with PP 35 2021 Article 40 paragraph 2 , Paragraph 3 , and Article 43 paragraph 1.Analysis of judges ' consideration at the Cassation level according to the principle of justice in the case of Decision No. 060 / Pdt.Sus-PHI/2023/PN MDN juncto decision No. 1174K / Pdt.Sus-PHI/2023 is acceptable.